Impact of Exchange Rate, and Foreign Direct Investment on External Debt: Evidence from Pakistan Using ARDL Cointegration Approach - Zahra, Andleeb; Nasir, Nadia; Rahman, Saif Ur; Idress, Sadia (iRASD Journal of Economics, 2023)
Using time series data from Pakistan 1973 to 2021, this research examines the effect of exchange-rate, fiscal deficits, foreign direct investment and economic expansion on foreign debt. The auto regressive distributed lag model is used in the research to look into the co-integration analysis of variables and their existence. The study confirms the positive and significant relationship exist among the rate of exchange, foreign direct investment, the fiscal deficit, economic growth, and external debt in the long run. However, in the short run, the real effective exchange rate and fiscal deficit are negatively related to the external debt, whereas the economic growth is positively related to the external debt. The policy maker recommended that rises the exchange rate, the value of a domestic currency falls to some extent, which improves the foreign exchange in which loans must be returned.